PENGARUH KARAKTERISTIK INDIVIDU DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING DI SDN TUGU UTARA 15 JAKARTA UTARA - Agung Astari, Muhammad; Diba Catur Putri, Fara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the effect of individual characteristics and organizational culture on elementary school teacher performance with work motivation as an intervening variable. A quantitative approach was conducted at SD Negeri Tugu Utara 15, North Jakarta, involving all 34 teachers through a saturated sampling technique. Data were collected using questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that individual characteristics do not have a significant effect on work motivation or teacher performance. In contrast, organizational culture has a positive and significant effect on work motivation and teacher performance. Work motivation also has a positive and significant effect on teacher performance, and organizational culture significantly influences teacher performance through work motivation. This study emphasizes the importance of organizational culture in improving elementary school teacher performance.